Apresentação PBCIB n.3, v.15, 2020 - Araújo, Vania Rodrigues Hermes de; Freire, Isa Maria; Freire, Gustavo Henrique de Araújo (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2020)
Apresentação PBCIB n.3, v.15, 2020